Human Immunodeficiency Virus and Leprosy Coinfection: Challenges in Resource-Limited Setups - Charles M. Kwobah; Kara K. Wools-Kaloustian; Jane N. Gitau; Abraham M. Siika (Case Reports in Medicine)
Mycobacteria leprae(leprosy) and HIV coinfection are rare in Kenya. This is likely related to the low prevalence (1 per 10,000 of population) of leprosy. Because leprosy is no longer a public health challenge there is generally a low index of suspicion amongst clinicians for its diagnosis. Management of a HIV-1-leprosy-coinfected individual in a resource-constrained setting is challenging. Some of these challenges include difficulties in establishing a diagnosis of leprosy; the high pill burden of cotreatment with both antileprosy and antiretroviral drugs (ARVs); medications’ side effects; drug interactions; scarcity of drug choices for both diseases. This challenge is more profound when managing a patient who requires second-line antiretroviral therapy (ART). We present an adult male patient coinfected with HIV and leprosy, who failed first-line antiretroviral therapy (ART) and required second-line treatment. Due to limited choices in antileprosy drugs available, the patient received monthly rifampicin and daily lopinavir-/ritonavir-based antileprosy and ART regimens, respectively. Six months into his cotreatment, he seemed to have adequate virological control. This case report highlights the challenges of managing such a patient.